Multi-trait GWAS identifies pleiotropic loci associated with colorectal cancer in East Asian populations - Chen, Xiqi; Zhu, Yong; Zhong, Peng; Xie, Guangdong (Frontiers in Genetics, 2025)
IntroductionWhile genome-wide association studies (GWAS) have identified numerous susceptibility loci in Colorectal cancer (CRC), most findings are based on European populations. Additionally, CRC shares genetic architecture with other traits, and multi-trait analysis can improve the discovery of pleiotropic loci.Materials and methodsWe conducted a multi-trait GWAS using the Multi-Trait Analysis of GWAS (MTAG) framework, leveraging large-scale genomic and phenotypic data from BioBank Japan (BBJ). We also examined genetic correlations between CRC and 70 complex traits, followed by local genetic correlation analysis and enrichment of heritability partitioned by chromatin states and tissue types.ResultsWe identified 25 genome-wide significant loci for CRC and colon polyps, including three novel loci in East Asian populations: BET1L (rs12226698, 11p15.5), OAS1 (rs2525858, 12q24.13), and BMP2 (rs4813802, 20p12.3). While BMP2 had been previously reported in European CRC studies, BET1L and OAS1 represent novel associations in East Asians. Colocalization analysis confirmed strong shared association signals between BET1L and OAS1 in CRC and colon polyps, supporting their pleiotropic effects in colorectal neoplasia. BET1L was further identified in the multi-trait analysis of CRC and myocardial infarction. Similarly, OAS1 was significantly associated with CRC and angina pectoris. Functional annotation revealed that these loci serve as expression quantitative trait loci (eQTLs) in colorectal tissues and immune-related pathways.ConclusionOur study identifies novel pleiotropic loci associated with CRC in East Asians, emphasizing the importance of population-specific genetic studies. The findings provide new insights into the genetic architecture of CRC and its shared pathways with other complex diseases.